Education and work incentives for frontline workers and household socioeconomic status influence delivery of health and nutrition interventions in Bihar, India - Avula, Rasmi; Kosec, Katrina; Holtemeyer, Brian; Tyagi, Parul; Hausladen, Stephanie; Menon, Purnima (Wiley, 2014)
In Bihar, India, coverage of essential nutrition interventions is low, but little is known about the factors associated with service delivery by FLW and utilization of services by HH. Data: A cross‐sectional survey of 790 FLWs and 6002 HH from 400 villages in 1 district in Bihar. Analysis: Multivariate regression analysis to examine supply‐ and demand‐side determinants of whether HH receive immunization, food supplements (FS), pregnancy care information (PCI) or nutrition information (NI). Supply side determinants varied by outcome: incentives for FLW were marginally positively associated (p<0.1) with immunization; FLW living outside their service areas was negatively associated with FS to HH (p<0.1); FLW education (p<0.05), use of pregnancy registers (p<0.05) and incentives (p<0.05) were positively associated with PCI. Demand side determinants varied by outcome: having a more educated HH head was associated with greater immunization; lower SES HH were more likely to get FS (p<0.05), but higher SES HH (p<0.05) and HH who had visited nutrition centers (p<0.05) were more likely to get NI. Conclusion: FLW education, proximity to area of service, and incentives affect service delivery outcomes, but HH factors are also important. Recruiting more educated candidates as FLW, investing in incentives, and enhancing HH contacts with nutrition centers through demand creation could improve service delivery outcomes.Grant Funding Source: Supported by Bill & Melinda Gates Foundation, through POSHAN led by IFPRI